Polyclonal HIV envelope-specific breast milk antibodies limit founder SHIV acquisition and cell-associated virus loads in infant rhesus monkeys. Issue 6 (November 2018) - Himes, Jonathon; Goswami, Ria; Mangan, Riley; Kumar, Amit; Jeffries, Thomas; Eudailey, Joshua; Heimsath, Holly; Nguyen, Quang; Pollara, Justin; LaBranche, Celia; Chen, Meng; Vandergrift, Nathan; et al.
Abstract Breast milk HIV-1 transmission is currently the predominant contributor to pediatric HIV infections. Yet, only 10% of breastfeeding infants born to untreated HIV-infected mothers become infected. This study assessed the protective capacity of natural HIV envelope-specific antibodies isolated from the milk of HIV-infected women in an infant rhesus monkey (RM), tier 2 SHIV oral challenge model. To mimic placental and milk maternal antibody transfer, infant RMs were i.v. infused and orally treated at the time of challenge with a single weakly neutralizing milk monoclonal antibody (mAb), a tri-mAb cocktail with weakly neutralizing and ADCC functionalities, or an anti-influenza control mAb. Of these groups, the fewest tri-mAb-treated infants had SHIV detectable in plasma or tissues (2/6, 5/6, and 7/8 animals infected in tri-mAb, single-mAb, and control-mAb groups, respectively). Tri-mAb-treated infants demonstrated significantly fewer plasma transmitted/founder variants and reduced peripheral CD4+ T cell proviral loads at 8 weeks post-challenge compared to control mAb-treated infants. Abortive infection was observed as detectable CD4+ T cell provirus in non-viremic control mAb- and single mAb-, but not in tri-mAb-treated animals. These results suggest that polyfunctional milk antibodies contribute to the natural inefficiency of HIV-1 transmission through breastfeeding and infant vaccinations eliciting non-neutralizing antibody responses could reduce postnatal HIV transmission.